2020
DOI: 10.3390/molecules25092062
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Access to 3,5-Disubstituted 7-(Trifluoromethyl)pyrazolo[1,5-a]pyrimidines Involving SNAr and Suzuki Cross-Coupling Reactions

Abstract: An efficient and original synthesis of various 3,5-disubstituted 7-(trifluoromethyl)pyrazolo[1,5-a]pyrimidines is reported. A library of compounds diversely substituted in C-3 and C-5 positions was easily prepared from a common starting material, 3-bromo-7-(trifluoromethyl)pyrazolo[1,5-a]pyrimidin-5-one. In C-5 position, a SNAr type reaction was achieved by first activating the C–O bond of the lactam function with PyBroP (Bromotripyrrolidinophosphonium hexafluorophosphate), followed by the addition of amine or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Jismy and co-workers developed protocols for PP derivatives synthesis based on 1,3-biselectrophilic ynones [ 47 , 48 , 49 ]. Unlike previous approximations, employing ynones delivers to hydroxy/enone substituents at position 5 of the fused pyrazole.…”
Section: Synthesis and Functionalizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Jismy and co-workers developed protocols for PP derivatives synthesis based on 1,3-biselectrophilic ynones [ 47 , 48 , 49 ]. Unlike previous approximations, employing ynones delivers to hydroxy/enone substituents at position 5 of the fused pyrazole.…”
Section: Synthesis and Functionalizationmentioning
confidence: 99%
“…They produce an exchange of hydroxyl group for a chloride atom by a NAS reaction; thus, employing optimized conditions for the coupling reactions could achieve aryls at position 5 like in product 79 ( Scheme 25 a) [ 48 ]. The reaction was further applied in the amine 3-bromosubstituted 81 and was optimized, finding the highly reproducible conditions to obtain 82 ( Scheme 25 b) [ 47 ]. The reaction shows an improvement in reaction times, and also, regarding the previous work, the authors found that modifying the ligand and catalyst enables the functionalization of the nucleophilic site at the pyrazolic moiety.…”
Section: Synthesis and Functionalizationmentioning
confidence: 99%
See 3 more Smart Citations